Mycobacterium abscessus Infection in Dermatomyositis with Calcinosis Cutis Universalis - Meirelles, Renata Travassos de Oliveira; Castro, Lucas Viana Alves; Fonseca, Gabriela Maria Rocha; Sousa, Anna Paula Mota Duque; Santiago, Mittermayer Barreto (Brazilian Journal of Case Reports, 2025)
Dermatomyositis (DM) is a rare autoimmune condition that may be complicated by calcinosis cutis, particularly in juvenile forms. In adults, extensive calcinosis is uncommon and once it ulcerates, it may lead to recurrent infections. Mycobacterium Abscessus is a rapidly growing nontuberculous mycobacterium (NTM) very rarely associated with DM, especially in disseminated infections. We report the case of a 28-year-old female with amyopathic DM and calcinosis cutis universalis who developed disseminated M. abscessus infection. The patient presented with cutaneous and pulmonary involvement, and M. abscessus was isolated from both skin fistulas and pleural effusion, demanding long-term antibiotic therapy. This is the fourth reported case of Mycobacterium Abscessus infection in a patient with dermatomyositis (DM), and the first linked to calcinosis cutis. This case underscores the importance of considering atypical mycobacterial infections in immunosuppressed patients with connective tissue diseases, especially when faced with recurrent or unusual infections. Furthermore, it highlights how skin barrier disruption caused by calcinosis may predispose immunocompromised individuals to such atypical infections.